Analisis Dampak Pandemi Covid-19 kepada Tingkat dan Struktur Ketergantungan dari Imbal Hasil Saham Perusahaan Farmasi di Indonesia periode 2019-2021 - Danisha, Ananda Tiara; Rizkianto, Eko; Prabowo, Hendro (Jurnal Manajemen dan Usahawan Indonesia, 2023)
This study aims to analyze the impact of the Covid-19 Pandemic on the degree and structure of dependence on the stock return of pharmaceutical companies in Indonesia that are listed on the IDX linearly with the Jakarta Composite Index (JKSE) within the period of 2019-202. This study also wants to see whether there is an effect of increasing searches for "Covid" on the stock return of these pharmaceutical stocks. The study found that there was an effect on the degree of dependence of stock returns which was positive but there were no significant changes in the structure of dependence. Meanwhile, it is known that online searches do not have a significant impact on pharmaceutical stock returns during the pandemic.